PENGARUH ATRIBUT PRODUK, CITRA MEREK, IKLAN DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Konsumen Sepatu Olahraga Nike di Kota Pontianak) - admin, RIZKY KURNIAWAN B11112041 (Jurnal Manajemen Update, 2016)
This research was conducted to examine and analyze the influence of Product Attribute, Brand Image, Advertisement, and Reference Group to the Purchase Decision of Nike Sport Shoes in Pontianak. This is a descriptive research and associative causal. The population in this research used purposive samping that involved 100 respondents as the sample. The sample criteria are respondents who wore Nike sport shoes at least 6 months, respondents who were at least 17 years old, respondets who ever watched advertisements of Nike Sport Shoes in some media, respondents who took the purchase decision. The technique in this research used the analysis of double linier regression. The research proved that the variable of Product Attribute, Brand Image, and Advertisement influenced a positive significance to the Purchase Decision, and the variable of Reference Group did not influence a positive significance to the Purchase Decision. The ability of the indenpendent variables in explaining the influence to the Purchase Decision is 59% and the other factors of the research model is 41%. Keywords: Product Attribute, Brand Image, Advertisement, Reference Group and Purchase Decision.